Combined statistical and mechanistic modelling suggests food and temperature effects on survival of early life stages of Northeast Arctic cod (Gadus morhua). (May 2015) - Stige, Leif Chr.; Langangen, Øystein; Yaragina, Natalia A.; Vikebø, Frode B.; Bogstad, Bjarte; Ottersen, Geir; Stenseth, Nils Chr.; Hjermann, Dag Ø.
Graphical abstract: Highlights: We combined statistical and mechanistic modelling of the early life stages of cod. Results suggest effects of copepod nauplii and temperature on cod survival locally. The variable survival may in turn influence the annual mean length of the young cod. The annual mean length of the young cod significantly predicts recruitment at age 3. Our modelling approach allows linking local-scale and population dynamics. Abstract: Understanding the causes of the large interannual fluctuations in the recruitment to many marine fishes is a key challenge in fisheries ecology. We here propose that the combination of mechanistic and statistical modelling of the pelagic early life stages (ELS) prior to recruitment can be a powerful approach for improving our understanding of local-scale and population-scale dynamics. Specifically, this approach allows separating effects of ocean transport and survival, and thereby enhances the knowledge of the processes that regulate recruitment. We analyse data on the pelagic eggs, larvae and post-larvae of Northeast Arctic cod and on copepod nauplii, the main prey of the cod larvae. The data originate from two surveys, one in spring and one in summer, for 30 years. A coupled physical–biological model is used to simulate the transport, ambient temperature and development of cod ELS from spawning through spring and summer. The predictions from this model are used as input in a statistical analysis of the summer data, to investigate effects of covariates thought to be linked to growth and survival. We find significant associations between the local-scale ambient copepod nauplii concentration and temperature in spring and the local-scale occurrence of cod (post)larvae in summer, consistent with effects on survival. Moreover, years with low copepod nauplii concentrations and low temperature in spring are significantly associated with lower mean length of the cod (post)larvae in summer, likely caused in part by higher mortality leading to increased dominance of young and hence small individuals. Finally, we find that the recruitment at age 3 is strongly associated with the mean body length of the cod ELS, highlighting the biological significance of the findings.